Lymphocytic colitis: clinical presentation and long term course. Issue 5 (1st November 1998) - Mullhaupt, B; Güller, U; Anabitarte, M; Güller, R; Fried, M
Abstract : Background —Lymphocytic colitis is characterised by chronic watery diarrhoea with normal endoscopic or radiological findings and microscopic evidence of pronounced infiltration of the colonic mucosa with lymphocytes. Aim —To investigate the long term clinical and histological evolution of the disease in a large group of patients with well characterised lymphocytic colitis. Methods —Between 1986 and 1995 the histological diagnosis of lymphocytic colitis was obtained in 35 patients; 27 of these agreed to a follow up examination. All clinical, endoscopic, and histopathological records were reviewed at that time and the patients had a second endoscopic examination with follow up biopsies. Results —The patients initially presented with the typical findings of lymphocytic colitis. After a mean (SD) follow up of 37.8 (27.5) months, diarrhoea subsided in 25 (93%) and histological normalisation was observed in 22 (82%) of the 27 patients. Progression from lymphocytic colitis to collagenous colitis was not observed. Conclusions —Lymphocytic colitis is characterised by a benign course with resolution of diarrhoea and normalisation of histology in over 80% of patients within 38 months. Considering the benign course of the disease, the potential benefit of any drug treatment should be carefully weighed against its potential side effects.